Efeito da terapia de fotobiomodulação na síndrome geniturinária da menopausa - Bezerra, Lívia Oliveira (2025)
Introduction: Aging is a universal and inevitable process that is attracting interest in many areas around the world. In women, in addition to the physiological changes resulting from age, other changes occur due to ovarian failure that culminates in menopause. During menopause, there is a decrease in the levels of female sexual steroids and, as a consequence, a spectrum of genitourinary symptoms and signs known as Genitourinary Syndrome of Menopause (GMS) is observed. GMS involves numerous urogenital changes, which imply changes in sexual and urinary functions. Objective: Article 1 - To conduct a systematic review with meta-analysis of clinical trials to evaluate the impact of photobiomodulation therapy (PBMT) on functional performance, covering aspects such as fatigue, strength and functional capacity in healthy individuals. Article 2 - To evaluate the effects of PBMT, both alone and in combination with pelvic floor muscle training (PFMT), on pelvic floor muscle (PFM) function, as well as on sexual function, urinary function and quality of life (QOL) in women affected by GMS. Methodology: Article 1 - A systematic review with meta-analysis was carried out from June to October 2022 in electronic databases, including Web of Science, Lilacs, Scielo, PubMed, Cochrane, Pedro, Embase, Science Direct, Scopus, Clinical Trials, Google Scholar, Open Gray and Trials Central, in addition to an active search in references of relevant studies. The following descriptors were used in combination: "Photobiomodulation Therapies" OR "Therapies Photobiomodulation" OR "Therapy Photobiomodulation" OR "Low-Level Light Therapy" OR "Diode Laser" AND "Muscle Strength" OR "Pain" OR "functionality" AND "Functional Capacity". There were no time and language restrictions in the search. Randomized clinical trials that used TFBM, Laser or LED as the only intervention and evaluated functional performance were included, while studies that compared other therapeutic modalities or involved participants with chronic diseases or acute injuries were excluded. Study selection was conducted by three independent reviewers via Rayyan, and data extraction was performed using a standardized form. Risk of bias was assessed using Risk of Bias 2 (RoB 2), and confidence in the evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Meta-analysis was conducted using RevMan software. Article 2 - Randomized, blinded clinical trial. Women aged 45 to 65 years with a diagnosis of sexual and urinary dysfunction participated in the study and were randomly divided into three groups: PFMT isolated group (GTMAP isolated, n=18), PFMT associated with active photobiomodulation (PBM) group (GTMAP + active PBM, n=18) and PFMT associated with sham PBM group (GTMAP + sham PBM, n=18). The volunteers were evaluated before the intervention and after eight weeks. The Female Sexual Function Index (FSFI) was applied to assess sexual function, the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) for urinary loss, the Patient Global Impression of Improvement (PGI-I) for the level of satisfaction after the intervention and vaginal manometry was also performed to assess pelvic floor muscle (PFM) functionality. The sample data were analyzed using the Jamovi statistical software (version 2.3.28). Results: Article 1 - Sixteen studies were included, totaling 340 participants (183 men and 157 women). Most studies had a low risk of bias and heterogeneity was observed in devices and application parameters. It was observed that BMFT improved recovery from fatigue (mean difference: 5.87; 95% CI 3.83, 7.91). There was no improvement in strength: peak torque (mean difference: 12.40; 95% CI -5.55, 30.55); one repetition maximum test (mean difference: 39.97, 95% CI -2.44, 82.38); isometric and isokinetic strength (mean difference: 2.77, 95% CI -14.90, 20.44) and there was also no improvement in short-term (mean difference: 0.67, 95% CI -0.58, 1.91) and long-term (mean difference: 18.44, 95% CI -55.65, 92.54) functional capacity. Article 2 - Significant differences were observed between groups over time for the ICIQ-SF (p=0.02), the FSFI (p=0.002) and their subscales: arousal (p=0.01), lubrication (p<0.001), orgasm (p=0.04) and satisfaction (p=0.007). The final manometry results showed significant differences between the groups: GPFMT + active PBM and GPFMT + sham PBM (mean difference 3.71; CI: 0.02, 7.40; d: 0.28) and GPFMT + sham PBM versus GIPFMT (mean difference: -1.05; CI: -2.06, -0.04; d: 0.07). Conclusion: Article 1 - TFBM is a resource that can help promote recovery from fatigue in healthy individuals; however, there is no evidence to support that the use of PBM can enhance strength and improve functional capacity in the short and long term. Article 2 - Treatment with active PBM combined with PFMT had a superior trend towards improving sexual function, urinary function and QOL in women with SGM. Although PBM has relevant therapeutic potential, its integration into conventional practice remains cautious due to the need for more research to establish standardized guidelines to establish long-term efficacy.